Growth of Eutypa lata in Grapevine Wood Extracts - Ferreira, J.H.S. (South African Journal of Enology and Viticulture, 2017)
Nitrogen and carbohydrate contents in extracts from Cape Riesling canes/shoots and wood were determined. Nitrogen content from extracts of both canes/shoots and wood was the highest during June, July and August. Sugar content from canes/shoots was highest during July and August, while the sugar content in wood was the highest during July, August and September. Growth of Eutypa lata was determined in these extracts in vitro. Eutypa lata had the highest mycelium yield when grown in canes/shoot extracts collected during July and August. Eutypa lata showed the best growth in extracts from wood collected during July. It is suggested that the high nitrogen and sugar content in grapevine wood could play a role in the susceptibility of pruning wounds during the pruning season (i.e. June to August) to Eutypa lata.